Hospital readmissions in the group of users on the Flexible Assertive Community Treatment – experiences from RECOVER E Montenegro samples - J. Dedovic; T. Djurisic; A. Tomcuk; A. Macic; N. Matkovic; D. Miladinovic; S. Vlahovic (European Psychiatry, 2022)
Introduction As a part of Horizon 2020 program, RECOVER-E project activities were initiated in Montenegro in 2018. The initial step involved a thorough situation analysis of the setting and circumstances of treatment of users with severe mental health illnesses, followed by the establishment of the community mental health team (CMHT) within the Special Psychiatric Hospital Kotor. The CMHT became responsible for the treatment of a group of clients with severe mental health illnesses, based on the principles of „Flexible Assertive Community Treatment (FACT – A Dutch model).